Third-Party Funds and Profit Margin as Determinants of Murabahah Financing Performance in Islamic Rural Banks: Evidence from BPRS Bahari Berkesan, Ternate City - Hasnin, Muhammad; Suar, Abi; Landola, Selfianti; Kotib, Mohammad; Nasar, Fahima; Taslim, Fadli Ali (Cita konsultindo, 2025)
The purpose of this study is to examine how profit margins and third party funding affect Murabahah contract financing (BPRS Bahari Berkesan, Ternate City). This study is quantitative. Secondary data from the Financial Services Authority (OJK) website, especially the Triulan financial report of BPRS Bahari Ternate, is used as a data source. Multiple linear regression analysis using SPSS version 26 software is the data analysis method used. The findings of the study revealed that (1) The growth of Murabahah contracts at BPRS Bahari Berkesan, Ternate City is greatly influenced by third party funds. (2) The findings of this study indicate that the profit margin variable has a significant effect on the financing of murabahah contracts, because the results of the hypothesis test indicate that the calculation value of the profit margin variable > t table (4.902 > 2.262) and the level of significance is < 0.05 (0.001 < 0.05). (3) further indicated by the significant probability value of 0.000, which is < 0.05 (0.000 < 0.05). This indicates that the financing of murabahah contracts with the BPRS Bahari Berkesan Ternate City Exchange Rate is greatly influenced by both the profit margin and DPK simultaneously.